From neurosexism to neurofeminism: A sociocentric reading of the debate on sex differences - Liotzis, Vangelis (The Greek Review of Social Research, 2026)
The article examines how the neurosexism approach is conceptualised and articulated. The general idea is that studies in the field of neurosciences that support significant and fixed biological sex differences should be considered instances of neurosexism. This is because they tend to reproduce gender stereotypes and lend credence to harmful biases by overlooking the complexity of human nature and social life. A sociologically oriented reading of the relevant literature confirms that a critical approach to neurosexism does not deny any biologically determined sex differences; rather, it attempts to ensure a full understanding of neuroscientific findings and their significance in reproducing gender inequality. This is attempted in the context of a distinct current in the field of neurosciences, that of neurofeminism, which favours intersectional approaches and productive interdisciplinary dialogue with the social sciences.